Transformer based multiple coupled LC tanks for on-chip VCO design and applications - Ma, Kaixue (2013)
A transformer based multiple coupled LC tanks model for on-chip VCO design is introduced. The merits of adoption multiple coupled LC tanks can be Q factor enhancement for the equivalent LC tank of VCO, low power consumption, better amplitude swing and broad tuning range can be obtained. As an illustration case two low power Ku band VCOs using dual LC-tanks with/without feedback designed using a 0.18 μm BiCMOS process for low phase noise or wide tuning range are demonstrated.